Mapping the temporal transcriptomic signature of a viral pathogen through CAGE and nanopore sequencing - Dóra Tombácz; Balázs Kakuk; Gábor Torma; Ádám Fülöp; Ákos Dörmő; Gábor Gulyás; Zsolt Csabai; Zsolt Boldogkői (PLoS ONE, 2025)
Introduction Equid alphaherpesvirus 1 (EHV-1), a veterinary pathogen belonging to the Varicellovirus genus, is responsible for significant economic losses in the global equine sector. This research involved timescale gene expression profiling and transcriptional reannotation of this herpesvirus. Methods We employed CAGE sequencing on the Illumina platform to determine transcript start sites, alongside long-read direct cDNA sequencing on Oxford Nanopore Technology platform to detect full-length viral transcripts. Samples were collected in triplicate at nine distinct stages of the viral lifecycle. We also applied protein synthesis inhibition to determine the immediate-early gene expression of the virus. Earlier data on native RNA sequencing was also utilized to validate the results. The sequencing data were processed using the LoRTIA and NAGATA software tools. Results The time-course analysis of viral transcript expression using long-read dcDNA-Seq enabled the characterization of these transcripts based on their kinetic behavior throughout the replication cycle. Furthermore, the study involved a comprehensive reannotation of the EHV-1 transcriptome. CAGE analysis helped identify the transcription start sites and promoter regions, while direct cDNA sequencing provided a more accurate approach to capturing full-length transcripts and isoform diversity. Through an integrated approach, we identified and validated numerous novel transcripts, thereby refining the EHV-1 transcriptome annotation. These methods allowed for a more detailed and accurate mapping of the EHV-1 transcriptome, uncovering previously unknown transcripts and refining the existing annotations. Conclusions The shifting patterns in transcript isoforms and overlaps suggest a sophisticated regulatory network that enables EHV-1 to precisely modulate gene expression throughout its replication cycle. The presence of multiple isoforms per gene indicates that the virus can adapt to different stages of infection by producing a variety of transcripts. This likely enhances its genomic efficiency and allows it to respond more effectively to the host’s environment.